2003
DOI: 10.3109/14992020309080050
|View full text |Cite
|
Sign up to set email alerts
|

Minimal response levels for visual reinforcement audiometry in infants: Niveles mínimos de respuesta en la audiometría por reforzamiento visual en niños

Abstract: The aim of this study was to determine normative values for minimal response levels (MRLs) for normal-hearing young infants using insert earphone visual reinforcement audiometry (VRA). The subjects were 46 normally developing infants aged between 33 and 50 weeks who had hearing sensitivity assumed to be within normal limits and no evidence of middle ear dysfunction. VRA was carried out using insert earphones with warble tone stimuli, generated from an AC33 audiometer and calibrated to ISO 389-2 for insert earp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…The four frequency threshold average for the tone-bursts (0.5-4.0 kHz) was 28 dBA SPL when based upon a d’ criterion of 1.0. There were no significant differences in infant threshold as a function of frequency found in the present study, although Olsho et al (1988) and Parry et al (2003) found elevated thresholds at 0.5 kHz in comparison to those at 1.0, 2.0 or 4.0 kHz. The Parry et al thresholds, when converted to dB SPL for insert phones in an occluded (adult) ear canal, were 26, 19, 19, and 22 dB SPL for 0.5, 1.0, 2.0 and 4 kHz, respectively, or a 4-frequency average of 21.5 dB SPL.…”
Section: Discussion Of Experiments IIcontrasting
confidence: 89%
“…The four frequency threshold average for the tone-bursts (0.5-4.0 kHz) was 28 dBA SPL when based upon a d’ criterion of 1.0. There were no significant differences in infant threshold as a function of frequency found in the present study, although Olsho et al (1988) and Parry et al (2003) found elevated thresholds at 0.5 kHz in comparison to those at 1.0, 2.0 or 4.0 kHz. The Parry et al thresholds, when converted to dB SPL for insert phones in an occluded (adult) ear canal, were 26, 19, 19, and 22 dB SPL for 0.5, 1.0, 2.0 and 4 kHz, respectively, or a 4-frequency average of 21.5 dB SPL.…”
Section: Discussion Of Experiments IIcontrasting
confidence: 89%
“…The 71% hit rate and a 21% false alarm rate for the vowel discrimination task is typical of that found in laboratory-based studies of infant perceptual responses using visually-reinforced operant procedures (Parry et al 2003; Hulecki & Small 2011; Casey & Small 2014). These lab-based studies of hearing thresholds for low-risk, typically developing infants have provided valuable age-specific norms for infant thresholds for tones, and also data that speak to the limitations of the method.…”
Section: Discussionsupporting
confidence: 54%
“…The age in months at behavioral evaluation was also included in the model, as previous studies have suggested that behavioral thresholds improve with age (e.g. Parry et al 2003). …”
Section: Methodsmentioning
confidence: 99%